SANOAT KLASTERLARINING HUDUD IMIJI VA RAQOBATBARDOSHLIGINI OSHIRISHDAGI OʻRNI VA AHAMIYATI (Marketing Journal, 2026)
AbstractThis paper examines how industrial clusters contribute to territorial branding andregional competitiveness from a marketing perspective. The study relies on a literaturereview and a comparative case analysis of Uzbekistan and selected internationalexamples. Findings suggest that cluster identity, synergy, and differentiation helpterritories build a unique selling proposition (USP); the “origin of production”mechanism strengthens trust and reputation, while export communications improvecluster brand visibility in international markets. The paper offers practicalrecommendations for applying the cluster approach to territorial branding andcompetitiveness policies.Keywords: industrial cluster; territorial brand; competitiveness; brandingstrategy; positioning; USP; customer loyalty